APAH: An autonomous IoT driven real-time monitoring system for Industrial wastewater - Nishant Chavhan; Resham Bhattad; Suyash Khot; Shubham Patil; Aditya Pawar; Tejasvi Pawar; Palomi Gawli (Digital Chemical Engineering)
Water pollution, worsened by rapid industrialization, poses severe challenges to global water management, particularly in developing countries like India. Conventional water quality monitoring methods, which rely on manual sampling and laboratory analysis are, inadequate for handling the dynamic and real-time nature of industrial wastewater contamination. To address this issue, this research article presents the state-of-the-art IoT-based autonomous real-time nonitoring system (APAH), a scalable and frugal solution for industrial wastewater management. APAH integrates multi-parameter sensors to continuously monitor critical water quality parameters such as pH, dissolved oxygen (DO), electrical conductivity (EC), total dissolved solids (TDS), turbidity, and temperature. The system's layered architecture, comprising a sensing layer, edge layer, and application layer, enables data acquisition, processing, and remote access via APAH i.e. developed Android mobile application, respectively. APAH utilizes advanced technologies including, the Internet of Things (IoT) and Machine learning (ML) to provide real-time monitoring and control of wastewater treatment processes. Automated valve controls and real-time alerts enable timely intervention, preventing contamination and ensuring compliance with environmental standards. The system's performance was validated through field tests at four industrial wastewater treatment plants in Maharashtra, India particularly directed towards textile, dairy, and greywater effluents, demonstrating significant improvements in water quality post-treatment. The APAH system offers a promising solution for enhancing industrial wastewater treatment efficiency and ensuring sustainable water resource management. By integrating IoT technologies, real-time monitoring, and predictive analytics, APAH can contribute to addressing the urgent need for effective water quality management in industrial environments, particularly in regions facing acute water scarcity and pollution challenges.